(untitled) (International Journal of Applied Research in Management and Economics, 2020)
This study aimed at examining the effect of internet services on online purchase intention of customers in Behpakhsh Company. Variables of this study included transaction services, pre-purchase services, Navigation experience, Attitude to the web, online purchase intention. Descriptive-survey method was used to examine hypotheses and respond to the questions. Statistical population consisted of customers of Behpakhsh Company. Statistical sample size obtained to 384 members. This study was implemented in Behpakhsh Company. To collect required data, researcher-made questionnaire was used. Moreover, regression analysis was applied in this research. Data analysis and hypothesis testing were done through SPSS Software. Findings obtained from this study indicated effect of internet services on customers’ online purchase intention in case of Behpakhsh Company.